Identification of poultry meat using random amplified polymorphic dna (rapd) technique - Ali Arslan; O. İrfan İlhak; Ö. Pelin Bozkurt; Pınar Şeker (Eurasian Journal of Veterinary Sciences)
In this study, meats of 8 poultry species (chicken, turkey, gull, ostrich, duck, goose, quail, partridge) ware identified by random amplified polymorphic DNA (RAPD) method using two different primers of 10 nucleotides each (primer 1- CAA TCG CCG T, primer 2- CCA CAG CAG T). A 45-cyclus PCR (each cycle; 45 s at 94°C, 45 s at 364C, and 60 s at 72°C) was performed for identification of poultry flesh. Results concluded that RAPD is a practical, rapid, and reliable method that can be used for identification of poultry meals in control of adulteration of consumers from exposure to the flesh thai the society normally does not consume.